Taking Global Citizenship Education (GCED) Beyond the Classroom: Analyzing the Advocacy Projects of GCED-Trained Educators in the Philippines - Andres, Brenson Y. (Alipato, A Journal of Basic Education; Vol 15 (2024): Alipato, A Journal of Basic Education, 2025)
Global Citizenship Education (GCED) has recently become an emerging movement in the field of international education. In the Philippines, while there is a lack of policy documents from the Department of Education (DepEd) mandating its implementation, GCED is already gaining momentum on the ground. Many school heads and teachers have been involved in GCED training programs organized by international and domestic institutions. Moreover, they have not only been busy integrating GCED into their teaching practices, but they have also initiated advocacy projects that bring GCED outside the classroom. Given this context, it is interesting to examine how Filipino GCED-trained teachers take on their roles not only as global citizenship educators but also as global citizens. Utilizing phenomenological research design with data collected from artifacts analysis and interviews of GCED-trained basic education teachers and leaders, this study addressed these research questions: (1) What advocacy projects have been implemented by GCED-trained teachers in the Philippines outside the confines of their classroom?; (2) What factors motivated them?, (3) What challenges did they face in the implementation?; and (4) Employing Franch’s (2020) GCED typology, what GCED discourse is dominant among the teachers based on these projects? Results showed that teachers implemented a diverse array of activities such as Sustainable Development Goals (SDGs) awareness raising, community service projects, development of GCED instructional materials, capacity building for teachers, youth empowerment programs, environmental projects, and cultural experience/intercultural exchange. They were motivated by different factors such as personal experience, issues with GCED implementation, influence of teacher training, and personal skills, interest, and passion, while they were challenged by lack of support from higher-ups, mindset of fellow educators, and lack of funding and resources. With the diversity of advocacy projects, the most dominant typology is cosmopolitan humanism. This can be attributed to the influence of teacher training programs, which played a huge role from the conceptualization to the evaluation of the projects. Given the dearth of literature on GCED teacher-led advocacy projects beyond the classroom, the given findings are valuable in understanding the role of teachers not only as global citizenship educators but also as proactive global citizens. Moreover, recommendations such as enacting a policy that mandates the teaching of GCED, adopting best practices of leading training institutions, and conducting more studies on GCED in the context of the Philippines were forwarded by the study.